Biofortification Priority Index (BPI), a composite crop-specific index that ranks countries according to their suitability for investment in biofortification - CGIAR Research Program on Agriculture for Nutrition and Health (2021)
HarvestPlus developed the Biofortification Priority Index (BPI) in 2013. The latest version has new varieties released data and the latest evidence on impact from 128 countries in Africa, Asia, and Latin America and the Caribbean.